Increased body mass index linked to decreased neutralizing antibody titers of inactivated SARS‐CoV‐2 vaccine in healthcare workers - Juan Hu; Mingcai Zhao; Yongmei Zhao; Wenjuan Dong; Xuemei Huang; Shaocheng Zhang (Wiley, 2023)
Abstract Objective Obesity is an important risk factor for COVID‐19. However, whether obesity affects SARS‐CoV‐2 antibody production is unclear. This study aimed to identify the influence of obesity on neutralizing antibody production of an inactivated SARS‐CoV‐2 vaccine to better guide vaccination strategies. Methods This cross‐sectional study recruited a total of 239 healthcare workers (age, 21-50 years) from Suining Central Hospital during 22-23 April 2021. An electronic questionnaire on basic characteristics was completed by all participants. A general physical exam and fasting blood sampling by venipuncture were performed. Peripheral leukocyte counts and the ratios of leukocyte subsets, hepatorenal function, and the neutralizing antibody titers against SARS‐CoV‐2 were measured. Results Among 239 healthcare workers, the participants with underweight, normal weight, overweight, and obesity accounted for 10.88%, 64.44%, 23.01%, and 1.67%, respectively. The highest peripheral monocyte counts were observed in the group with obesity, whereas the lowest were observed in the group with normal weight. Similar results were obtained with respect to percentage of peripheral monocytes. Participants with obesity had higher peripheral eosinophil counts and percentages than the other three groups. The median neutralizing antibody titer was 12.70 AU/mL, with 85.36% (n = 204) of participants were sufficiently protected against SARS‐CoV‐2. The lowest neutralizing antibody titers were observed in the group with obesity, whereas the highest were observed in the group that was underweight. Additionally, high BMI was significantly associated with high peripheral monocyte counts [B (95% CI) = 0.008 (0.002, 0.013)] and low neutralizing antibody titers [B (95% CI) = −1.934 (−3.663, −0.206)]. Conclusions Obesity could induce chronic inflammation, and associated with lower neutralizing antibody titers against SARS‐CoV‐2 after inactivated SARS‐CoV‐2 vaccination.